Family Interview for Brain Death and Tissue-organ Donation - Kerem Erkalp (Galenos Yayinevi, 2023)
After brain death, a family interview is required to discuss organ donation requests and procedures with the donor's relatives. This interview process requires knowledge, communication skills and experience for the interviewers. Effective and sincere communication is the main key to a successful family interview. A family interview should be planned and a method with certain characteristics should be followed and it should be pre-structured and include a conscious dynamism regarding the content and direction of the interview and the possibility of organ donation.